ANTISENSE MODULATION OF ACTIVATING TRANSCRIPTION FACTOR 3 EXPRESSION - BAKER, BRENDA, F; DOBIE, KENNETH (2003)
Antisense compounds, compositions and methods are provided for modulating the expression of activating transcription factor 3. The compositions comprise antisense compounds, particularly antisense oligonucleotides, targeted to nucleic acids encoding activating transcription factor 3. Methods of using these compounds for modulation of activating transcription factor 3 expression and for treatment of diseases associated with expression of activating transcription factor 3 are provided. La présente invention concerne des composés, des compositions et des procédés antisens qui permettent de moduler l'expression du facteur de transcription activateur 3. Les compositions de l'invention comprennent des composés, en particulier des oligonucléotides antisens, qui ciblent des acides nucléiques codant le facteur de transcription activateur 3. L'invention se rapporte également à des procédés d'utilisation desdits composés pour moduler l'expression du facteur de transcription activateur 3 et pour traiter des maladies associées à l'expression du facteur de transcription activateur 3.